One Pot Synthesis of 3-Nitro-1,2-dihydroxyanthraquinone and 1-Hydroxy-9,10-dioxo- 9,10-dihydroanthracen-2-yl Benzoate Using Microwave Irradiation - Jain, Khushboo; Singh, Sadhana (Asian Journal of Chemistry, 2010)
An efficient method for the one pot synthesis of 3-nitro-1,2-dihydroxyanthraquinone and 1- hydroxy-9,10-dioxo-9,10-dihydroanthracen-2-yl benzoate (an anthraquinone derivative) under microwave irradiation conditions. The structures of newly synthesized compounds have been established by analytical data that includes elemental analysis, mass spectra, IR spectra and melting point.